Effect of mulching on soil fertility, biomass production and nutrient uptake of maize (Zea mays L.) in a degraded land - Laxminarayana, K.; Bhatt, B.P.; Swer, Mildonna (Indian Journal of Agroforestry, 2020)
A field experiment was conducted during kharif 2004 in a degraded wasteland at ICAR Research Complex for NEH Region, Umiam, Meghalaya to study the effect of mulching of some prominent multipurpose trees on biomass production of maize and their residual effect on soil fertility under Alder based agro forestry system. Significantly higher grain and stover yields were recorded with the incorporation of leaf biomass of Flemingia followed by Indigofera and Tephrosia. The results of the study revealed that mulching of Indigofera produced highest biomass (60.56 t ha-1) followed by Flemingia (52.25 t ha-1) and Tephrosia (45.27 t ha-1) with a yield response of 21-100 per cent over control. Highest uptake of N, P and K by grain and stover was recorded with the mulching of Indigofera followed by Flemingia and Tephrosia. In addition to biomass production of maize, mulching of multipurpose trees improve the organic matter status of the degraded land and available nutrient status of the soil. The study indicated that incorporation of leaf biomass of different tree species not only helps in higher crop productivity but also improves the fertility status of the soil.